Upaya Meningkatkan Keterampilan dan Prestasi Belajar Siswa dengan Metode Make a Match dan Picture and Picture pada Mata Pelajaran IPS Kelas I Sekolah Dasar - Mu'arifah, Ida Ayuning (Jurnal Pendidikan Dasar, 2021)
The purposes of this research are describing the learning with Make a Match and Picture and Picture Methods and analyzing the improvement of the learning achievement about Family Tree and Kinship in Social Science with Make a Match and Picture and Picture Methods on the First Grade Students of Sukoharjo General Elementary School, First Semester of 2017/2018 Academic Year. This research is a Classroom Action Research (CAR), occurred on august 2017. The subjects of this research are 19 students; consist of 11 boys and 8 girls. The results of this research are the learning on the small groups and match the pair of the cards correctly and the learning achievement improved, from average on 59,47 and completeness on 26,31% into average on 83,15 and completeness on 94,73%.